Penggunaan DDGS (Distillers Dried Grain with Solubles) jagung sebagai sumber protein nabati pakan benih ikan gurame Osphronemus goramy Lac. - Muhamad Agus Suprayudi; Upmal Deswira; Mia Setiawati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2013)
Two experiments were conducted to evaluate the utilization of corn distillers dried grain with soluble (DDGS) as plant raw material for giant gourami Osphronemus goramy diet. The digestibility of protein and dry matter was observed in the first experiment by using indirect methods and Cr2O3 was used as a tracer. A forty days feeding experiment was performed on the second stage of experiment to observe the effect of DDGS levels on the growth and feeding performance of giant gourami. The juvenile giant gourami were used in the experiment with initial weight around 4.7±0.78 g and reared in aquarium (35 x 40 x 50 cm3) and filled with 50 L treated water at a density of 0.2 fish L